Composition of the Essential Oil of Rosa damascena Mill. from South of Iran: Composition of the essential oil of Rosa damascenea - Mahmoodreza Moein,; Younes Ghasemia,; Forough Karami,; Hossein Tavallali, (Iranian Journal of Pharmaceutical Sciences, 2010)
The essential oil obtained by hydrodistillation of the aerial parts of Rosa damascenaMill. (Rosaceae) was analyzed by gas chromatography/mass spectrometry (GC/MS). The yield of the oil was 0.16% (v/w). Among 25 components, eight components, representing 99.98% of the oil, were characterized. Nonadecane (39.73%), heneicosane (32.38%), docosane (7.34%), citronellol (6.14%) and 9-nonadecene (5.69%), were found to be major constituents.